Strength feminism in diplomacy culture: A case study of Central Javanese female puppeteers - Harini, Setyasih; Arlinda, Silvi Aris (Technium Social Sciences Journal, 2024)
This study examines the role of female puppeteers in cultural diplomacy through the performing arts of wayang skin in Central Java. Wayang leather, which has been recognized by UNESCO as a World Cultural Heritage, functions as a medium of cultural communication rich in educational, moral, and historical values. The role of female puppeteers, despite facing patriarchal challenges, is increasingly growing thanks to the use of digital technology such as social media. This study uses a qualitative approach with a case study method, using interviews, observations, and documentation analysis to understand the contribution of female puppeteers in promoting Indonesian culture at the global level. The results show that female puppeteers not only maintain traditional arts, but also introduce new, more inclusive narratives in cultural diplomacy. Through platforms such as YouTube, female puppeteers are able to reach global audiences, strengthen Indonesia’s positive image, and influence international perceptions of gender equality in art and culture. This study enriches the literature on cultural diplomacy by highlighting the power of femininity as soft power in international relations, especially in facing the challenges of modernization and cultural glotion.